The Method of English Language Learning at Cambridge English Course Balikpapan - Waladdin Panggabean (Universitas Cokroaminoto Palopo, 2018)
English teachers should be smart in choosing a right method to be used in their teaching and learning. In the case of choosing any technique, method, model, and strategy is such a main priority before coming to class. The fallacy of choosing method in teaching can be a contradiction to the instructional objectives. The theoretical analysis tries to re-unlock any new perspective by using direct method in conducting English teaching and learning process. The way of interpretation and manipulation of method appropriately not only can enhance the quality of teaching and learning process but also leaning outcome or students’ achievement. Using direct method in teaching English is not only in spoken aspect but also in written one especially in teaching language skills, such as speaking, and grammar aspect. Applying direct method in teaching and learning English should pay attention to the students and the characteristics of the materials that will be taught. To teach and learn English as a foreign language and target language is good for the teachers or learners use the direct method.